The use of fetal neurosonography and brain MRI in cases of cytomegalovirus infection during pregnancy: A retrospective analysis with outcome correlation. (29th December 2017) - Birnbaum, Roee; Ben‐Sira, Liat; Lerman‐Sagie, Tally; Malinger, Gustavo
Abstract: Objective: To analyze ultrasound (US) and magnetic resonance imaging (MRI) results and developmental outcome in cases of maternal primary cytomegalovirus (CMV) infection during pregnancy. Methods: We retrospectively reviewed the results of fetal neurosonography and brain MRI of CMV‐infected fetuses (Group 1). Cases of maternal infection in which the fetal status was unknown, and subsequently had a negative CMV postnatal urine analysis, were independently analyzed (Group 2). Imaging results were classified as follows: positive, negative, or inconclusive . Developmental landmarks were followed up. Results: Eighty‐one women were included in the study: 48 (59.2%) in Group 1 and 33 (40.8%) in Group 2. In Group 1, termination of pregnancy was performed in 8 cases (16.7%) following the diagnosis of brain abnormalities. Among the remaining cases, concordance rate between US and MRI was 78%. False negative rates for US and MRI were 5.5% and 6.4%, respectively (hearing deficits). For MRI, we found 17.5% of false positive/inconclusive results, while for the US, we found 5% of inconclusive results. In Group 2, false positive rates for US and MRI were 6.5% and 12.9%, respectively. Conclusions: Adding MRI in CMV‐infected cases with a normal neurosonographic follow‐up should be weighed against a nonnegligible rate of false positive and inconclusive findings. Abstract : What's already known about this topic? Normal findings on serial dedicated neurosonography of CMV‐infected fetuses, performed by specialists in a referral center, are a reliable tool for parental reassurance regarding a favorable developmental outcome. What does this study add? The addition of brain MRI in cases of fetal infection and normal serial neurosonography is relatively small and should be weighed against the nonnegligible rate of false positive or inconclusive findings.